The rule of law, legal traditions, and economic growth in East Asia - Meredith Woo-Cumings (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper examines the literature on the rule of law and economic development, and in particular the influential argument by La Porta et al., on the superiority of the Anglo- American common law system in fostering financial development. In this paper I show that however compelling their argument might be, legal traditions and institutions do not determine the nature of the state, nor its likely role in the economy—nor do they critically determine the course of economic development. I build my case by examining the real and informal mechanisms of state intervention in the economy in East Asia. – law ; economic growth ; East Asia
Keywords: K10; O17; O57; 330; Rechtsstaat; Wirtschaftswachstum; Ostasien